Metazoan Diversity and Its Drivers: An eDNA Survey in the Pacific Gateway of a Changing Arctic Ocean - Gerlien Verhaegen; Tatsuya Kawakami; Ayla Murray; Akihide Kasai; Charlotte Havermans (Environmental DNA)
ABSTRACT Climate change drives species to adapt or undergo range shifts to survive. The Arctic Ocean, experiencing more drastic environmental changes than any other ocean, has two primary inflow regions that facilitate these shifts: the wide, deep Atlantic Gateway and the narrow, shallow Pacific Gateway. Environmental DNA (eDNA) surveys have proven to be effective in characterizing community composition and understanding its ecological drivers. We conducted the first COI marker‐based eDNA survey in the Pacific Gateway that analyzed seawater samples from various geographic regions, depths, and water masses across the Bering Strait, the Chukchi Sea, and the South Beaufort Sea. Metazoan taxa from 15 different phyla and indicator species for various regions and water masses were identified. We characterized a highly diverse neritic fauna in the Bering Strait and Chukchi Sea, aligning with known locations of benthic hotspots. On the slope of the Beaufort Sea, we observed transitions from copepod‐dominated epipelagic waters to cnidarian‐ and sponge‐dominated deeper areas. Alpha diversity peaked near the seabed and coastlines and was the highest within the warmest Alaskan Coastal Water mass. We linked metazoan communities to different environmental variables, with the community in the Bering Strait being associated with higher temperatures and fluorescence, and the majority of them with lower salinities. This included mostly Pseudocalanus copepod species and verongiid sponges. While rising temperatures might enhance alpha diversity, we anticipate this will primarily be due to the influx of warmer and fresher water masses. Several benthic taxa, including the bivalve Macoma calcarea and seastar Leptasterias arctica, as well as the jellyfish Chrysaora melanaster and the copepod Triconia borealis, were associated with colder, saltier waters and will likely be negatively impacted by ongoing environmental change. Our study successfully characterized changes in metazoan communities across the geographic regions and water masses within the Pacific Gateway of the rapidly changing Arctic Ocean.